USAHA MAGGOT (LARVA HERMETIA ILLUCENS) OLEH IBU RUMAH TANGGA DALAM UPAYA MENINGKATKAN PENDAPATAN KELUARGA DI POSBINDU DAHLIA RW 001 PETUKANGAN SELATAN - Deden Kurniawan; Syaiful Anwar; Selamet Riyadi; Muhammad Hadi Maulidin Nugraha (Jurnal Padamu Negeri, 2025)
Waste management is a global issue and not a glamorous topic. On the global stage, climate and development discussions related to waste management have not yet become a top priority. Despite facing a global climate crisis, pollution, and biodiversity loss, the issue of waste management remains neglected, even at the household level. In Indonesia, the Integrated Waste Management Sites (TPST) are still predominantly managed through operational systems such as controlled landfills, open dumping, and sanitary landfills, which create mountains of toxic waste that pollute the air, contaminate water, harm public health, and accelerate environmental degradation. 54.43% of waste in Indonesia comes from households, with the total in 2024 reaching 19,502,650.23 tons, and 8,046,428.49 tons (41.26%) of household waste remains unmanageable. The impact of the COVID-19 pandemic has led to a decrease in household income, prompting community service activities aimed at solving two problems simultaneously: waste management and efforts to increase household income. As part of this initiative, the introduction of maggot farming technology (Hermetia illucens larvae) was implemented to improve household income. The community service was carried out at Posbindu Dahlia RW 001, Petukangan Selatan, as the area is a residential neighborhood with available vacant land not yet utilized by the operators of the Jakarta Outer Ring Road toll. This community service activity ran smoothly, achieving all its targets and bringing about changes in the knowledge and behavior of the participants, as well as enabling them to optimize small land areas for maggot cultivation, thereby increasing household income.